HIGH SKILLED WORKERS MOBILITY IN SPAIN AND EUROPE: MOTIVATIONS AND IMPLICATIONS (Revista Galega de Economía)
Competing today through innovation requires attracting and retaining a high-skilled workforce. Compared to less skilled workers, high-skilled workers have a higher mobility. In order to help businesses and governments to create strategies that leverage or counter this high mobility of workers, this research explores the motivations and implications of regional concentration for high-skilled workers. The study analyses how the characteristics of the labor market and the dynamics of agglomeration of knowledge create incentives for the local concentration of engineers and scientists. The concentration of high-skilled workers is studied in Spain and Europe. At the empirical level the research shows how strong are the flows of workers moving from less-innovative regions to Madrid and Catalonia, since in some of these less-innovative regions more than 40 per cent of science and engineering engineers migrate. In Europe, the results show two coexistent phenomena: islands of innovation in some countries that attract most of the high-skilled workforce from that country and valleys of innovations formed by interconnected innovative regions. These regional concentrations of engineers and scientists are explained by unemployment rates of skills-exporting regions and greater concentrations of innovative activities. In this sense, the results suggest that the prospects for a future professional career rather than wage disparity is the most influencing factor in the regional concentration of high-skilled workers.